Broomrape occurrence in natural populations of annual Helianthus sp. - Poverene, María Mónica (2014)
Wild annual Helianthus species native to North America have demonstrated to be a valuable genetic resource for sunflower crop improvement. The search of genes for broomrape (Orobanche cumana Wallr.) resistance demonstrated a natural resistance to this parasitic weed in a wild sunflower species, H. petiolaris. This species along with the wild H. annuus form natural populations in extended areas of Argentina. In Europe, mostly the wild H. annuus is found across the main sunflower crop production areas. This species seems to be susceptible to the specialized parasitic weed, native from Europe. The environment and plant phenotypes of five wild H. annuus populations in their natural habitats in Argentina were compared to agrestal populations of H. annuus attacked by broomrape, located in Fernan Nuñez, Spain, and Kovilovo, Serbia. The study comprised four susceptible H. annuus and five resistant H. petiolaris populations. The goal was to realize if wild populations in Argentina could be in risk to be invaded by the parasitic weed. The plant morphology was not affected by the broomrape attack in Spain. Cluster analysis based on morphology showed differences among the two annual species but grouped H. annuus natural populations from Argentina and Europe. Clustering of ecological variables did not separate species and geographical localization. No differences in the environment for broomrape attacked and susceptible populations were found. Natural H. petiolaris populations could be considered a genetic resource for resistance against broomrape but natural H. annuus populations should be considered as a potential reservoir of the parasitic weed.